Fertilization levels with NPK in bush pea (Pisum sativum L.) genotypes under Andisol soil - Criollo, Manuel Fernando; Rodríguez, Daniel Marino; Checa, Óscar Eduardo; Ruíz Erazo, Hugo (Revista de Ciencias Agrícolas, 2025)
Pea (Pisum sativum L.) farmers in Colombia, especially in Nariño, lack knowledge about the appropriate fertilizer dosage needed to achieve optimal crop yields, resulting in reduced product competitiveness in the market. The objective was to evaluate the effect of six levels of NPK fertilization on yield components of four promising lines of bush pea with the afila gene in four municipalities in the Nariño department. A split-plot design with three replications was used in the experiment. The principal plot corresponded to the four promising lines of bush pea with the afila gene, and the subplot corresponded to six levels of fertilization. The results showed differential responses of the genotypes to different levels of fertilization. Based on the number of pods per plant, within the ARB15 line in Yacuanquer and ARB16 in Pasto, the result of the 120-16-56 fertilization level was higher than the recommended level based on soil analysis. In number of grains per pod, fertilization based on soil analysis showed similar results to the other five fertilization levels that were evaluated within the four pea lines in the different locations, except in Pasto within the ARB12 line, where 7.45 grains per pod were obtained, being lower than that obtained by the 120-6-56 level, which was 9.02. In terms of yield, the lines ARB2, ARB12, and ARB16 did not present a superior response to the fertilization level applied based on soil analysis. The best yield for ARB15 was obtained with a fertilization level of 90-12-42 in two locations.